J. Nelson Wisner, Ordinances and By-Laws of the Corporation of Martinsburg: Berkeley Co., West Virginia, Including the Act of Incorporation and All Other Acts of a Special or General Nature, at 76, An Ordinance in Relation to Pistol Galleries, § 1 (1875) - (:unkn) unknown (General Publisher, 1875)
Be it ordained by the Council of the Corporation of Martinsburg, That no pistol gallery, in which air guns or pistols, or guns or pistols in which are fired powder, is used, shall be established or carried on within the limits of the Corporation of Martinsburg by any person or persons, until the person or persons desiring to establish or carry on the same shall first obtain from the Mayor, attested by the Clerk of the Corporation, a permit authorizing the person or persons therein named to prosecute said business, and designating the place at which the same is to be carried on.
--
Keywords: SHOOTING RANGES OR GALLERIES